Bi-directional evolutionary topology optimization of continuum structures subjected to inertial loads. (May 2021) - Han, Yongsheng; Xu, Bin; Wang, Qian; Liu, Yuanhao
Highlights: The stiffness-based topology optimization model under inertial loads is proposed. Self-weight, centrifugal forces, the magnitude and direction of the additional acceleration are considered. Inertial loads have great influence on the topological structure, especially when fixed external force is small. The inertial loads change the magnitude and variation trend of objective function. The iterative curves converge to constant values stably, and the convergence rate is fast. Abstract: This paper proposes to investigate topology optimization of continuum structures with density-dependent inertial loads which including self-weight, centrifugal forces, the magnitude and direction of the acceleration of inertial loads in order to make topology optimization more realistic. By using an extended bi-directional evolutionary structural optimization (BESO) method, this work presents an extension of this procedure to deal with maximum stiffness (minimum compliance) topology optimization of continuum structures when different combinations of inertial loads and fixed forces are applied. Notably, the magnitude and direction of the acceleration of inertial loads are considered. The computation of the element sensitivity numbers is deduced in detail in order to achieve the optimum design. MATLAB programming of proposed mathematical approach is done and compared with the conventional structural optimization problems with fixed external force. The procedure has been tested in several 2D and 3D benchmark examples to illustrate and validate the approach. The inertial loads have great influence on the topological structure, especially when the fixed external force is relatively small. The inertial loads change the magnitude and variation trend of objective function. The iterative curves converge to constant values stably, and the convergence rate is fast.